Strangers on a train [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Chandler, Raymond, 1888-1959; Ormonde, Czenzi, 1906-2004; Bogdanovich, Peter, 1939-2022; Granger, Farley; Walker, Robert, 1918-1951; Roman, Ruth, 1922-1999; Carroll, Leo G., 1886-1972; Highsmith, Patricia, 1921-1995 (Distributed by Warner Home Video, 2004)
This film is about two strangers who accidentally meet and plan to trade murders. The screenplay of Patricia Highsmith's novel was adapted by Raymond Chandler.